Islamic-Based Financial Management; Study of Islamic Educational Values in the Management of BOS Funds at Batunisung Elementary School, Sumbawa - Sumiadi, Raden (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Management of School Operational Assistance funds, abbreviated as BOS, requires appropriate, good, transparent and responsible governance. In terms of planning and using BOS funds, it is very important to integrate the values of Islamic education to realize the right target use of BOS funds. This research aims to analyze the application of values in Islamic education in the planning and implementation of the school operational assistance program at SDN Batunisung. To obtain valid data, the research was designed using a penomenological approach, where the data obtained was based on phenomena that occurred at SDN Batunisung. The data obtained was then processed using the Miles and Huberman model. To test the validity of the data, researchers used data triangulation, namely source triangulation, technical triangulation and time triangulation. The results of the research show that the values of Islamic education have become the basis for the practice of managing School Operational Assistance (BOS) funds at SDN Batunisung, such as the values of honesty, trust, cooperation and sincerity. This is proven by the transparency of planning, involvement of all school parties, and responsibility in implementing the program.